Multiple-Resistance of Pyrazosulfuron-ethyl-Resistant Hoorahgrass (Fimbristylis miliacea L. Vahl.) in Paddy Fields in Central Thailand - Sripeangchan, Mongkol; Pornprom, Tosapon (Faculty of Agriculture University of Brawijaya in collaboration with PERAGI, 2026)
Hoorahgrass (Fimbristylis miliacea L. Vahl.) is one of the most yield-limiting weeds in paddy fields. Farmers have reported that hoorahgrass was unaffected when sprayed with the labeled rate (18.75 g a.i./ha) of the ALS-inhibiting herbicide pyrazosulfuron-ethyl. This study was conducted to confirm the suspected hoorahgrass resistance to pyrazosulfuron-ethyl in the paddy field. Additionally, cross-resistance to ALS-inhibiting herbicides across five chemical families and multiple-herbicide resistance via other mechanisms of action were evaluated. Both susceptible and resistant-hoorahgrass biotypes were examined at I50 based on visual injury and GR50 based on plant height and fresh weight. The resistance level of the resistant hoorahgrass biotype was 49.91-70.16 times higher than that of the susceptible biotype. The result of cross-resistance to ALS-inhibiting herbicides from different chemical groups indicated that pyrazosulfuron-ethyl-resistant hoorahgrass was not controlled at the labelled rate of ethoxysulfuron, bensulfuron-methyl, metsulfuron-methyl, bispyribac-sodium, penoxsulam, pyribenzoxim and triafamone. Additionally, resistance to other herbicide mechanisms of action did not confer cross-resistance to carfentrazone-ethyl, propanil, 2,4-D dimethylammonium, and florpyrauxifen-benzyl. Therefore, farmers should alternate herbicides with different mechanisms of action to effectively control pyrazosulfuron-ethyl-resistant hoorahgrass.